2018
DOI: 10.1186/s13002-018-0233-8
|View full text |Cite
|
Sign up to set email alerts
|

Traditional knowledge and cultural importance of Borassus aethiopum Mart. in Benin: interacting effects of socio-demographic attributes and multi-scale abundance

Abstract: BackgroundEliciting factors affecting distribution of traditional knowledge (TK) and cultural importance of plant resources is central in ethnobiology. Socio-demographic attributes and ecological apparency hypothesis (EAH) have been widely documented as drivers of TK distribution, but their synergistic effect is poorly documented. Here, we focused on Borassus aethiopum, a socio-economic important agroforestry palm in Africa, analyzing relationships between the number of use-reports and cultural importance on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 54 publications
2
32
0
8
Order By: Relevance
“…Indeed, Indigenous knowledge is often unevenly distributed among those factors [13]. Moreover, the level of individual knowledge of native plant species can be affected by many factors such as sex, age, ethnicity, occupation, religious and cultural beliefs, abundance, and the usefulness of the species [13, 17]. In addition, research conducted in the West African Sahel reported that the Fulani , Kel Tamashek , Bellah , and Maure groups were the main major livestock-rearing groups, while the farmers were mainly from the Bambara , Hausa , Djerma , Gourmantche , Mossi , and Soninke [13, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Indigenous knowledge is often unevenly distributed among those factors [13]. Moreover, the level of individual knowledge of native plant species can be affected by many factors such as sex, age, ethnicity, occupation, religious and cultural beliefs, abundance, and the usefulness of the species [13, 17]. In addition, research conducted in the West African Sahel reported that the Fulani , Kel Tamashek , Bellah , and Maure groups were the main major livestock-rearing groups, while the farmers were mainly from the Bambara , Hausa , Djerma , Gourmantche , Mossi , and Soninke [13, 18].…”
Section: Introductionmentioning
confidence: 99%
“…According to Geng et al [38], the transmission of knowledge from the older to the younger generation is nowadays confronted with a gradual disappearance of these knowledge systems partly due to migration from rural to urban areas. Several other studies including those of Lougbégnon et al [39] and Salako et al [15] have shown that individual characteristics such as age, for example, can influence knowledge of resources and their use within a community. The difference observed in medicinal use of the plant can be explained by the fact that such uses are often specific and are mostly reserved for the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…erubescens in Burkina Faso. These use-categories are also the most important for Bombax costatum [41], Lannea microcarpa [9], and Borassus aethiopum [15]. Food and medicinal uses are basic needs for local population living in Boulon, Tapoa-Boopo, and Tiogo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La VU est la moyenne des nombres d'usages assignés par les enquêtés à chaque essence : (Phillips et Gentry, 1993 ;Fandohan et al, 2017) avec U i : nombre d'usages mentionnés par l'informateur i du groupe social, variant de 0 à 4 ; N : nombre total d'informateurs interviewés par modalité de chaque facteur. La valeur d'usage calculée suit une distribution de Poisson puisqu'il s'agit de la moyenne d'une variable de comptage (Salako et al, 2018). Ainsi, un modèle linéaire généralisé (GLM) de la famille des lois de Poisson a été réalisé pour tester l'effet séparé de chacun des cinq facteurs sociaux sur la VU.…”
Section: Groupe Socioculturel Mahi Nago Anii Kotokoli Dendi Bariba Hounclassified